Ring Shadowing Effects on Saturn's Ionosphere: Implications for Ring Opacity and Plasma Transport. Issue 19 (4th October 2018) - Hadid, L. Z.; Morooka, M. W.; Wahlund, J.‐E.; Moore, L.; Cravens, T. E.; Hedman, M. M.; Edberg, N. J. T.; Vigren, E.; Waite, J. H.; Perryman, R.; Kurth, W. S.; Farrell, W. M.; et al.
Abstract: We present new results obtained by the Radio and Plasma Wave Science Langmuir probe on board Cassini during the Grand Finale. The total direct current sampled by the Langmuir probe at negative bias voltage is used to study the effect of the ring shadows on the structure of the Kronian topside ionosphere. The D and C rings and the Cassini Division are confirmed to be optically thin to extreme ultraviolet solar radiation. However, different responses from the opaque A and B rings are observed. The edges of the A ring shadow are shown to match the A ring boundaries, unlike the B ring, which indicates variable responses to the B ring shadow. We show that the variable responses are due to the ionospheric plasma, more precisely to the longer chemical lifetime of H + compared to H 2 + and H 3 +, suggesting that the plasma is transported from the sunlit region to the shadowed one in the ionosphere. Plain Language Summary: As Saturn's northern hemisphere experienced summer during the Grand Finale, the planet's northern dayside hemisphere and its rings were fully illuminated by the Sun. However, the southern hemisphere was partly obscured because of the shadows cast by the A and B rings. Using the in situ measurements of the Langmuir probe part of the Radio and Plasma Wave Science investigation on board the Cassini spacecraft, we study for the first time the effect of the ring shadows on Saturn's ionosphere. From the ring shadows signatures on the total ion current collected by the Langmuir probe, we show that the A and B rings are optically thicker (to the solar extreme ultraviolet radiation) than the inner C and D rings and the Cassini Division to the solar extreme ultraviolet radiation. Moreover, we reproduce the boundaries of the A ring and the outer edge of the B ring. Furthermore, observed variations with respect to the inner edge of the B ring imply a delayed response of the ionospheric H + because of its long lifetime and suggest that the ionospheric plasma is transported from an unshadowed region to a shadowed one in the ionosphere. Key Points: The D, C, and the Cassini Division are confirmed to be optically thin to extreme ultraviolet radiation, unlike the A and the B rings The total current collected by the Langmuir probe is lower at the inner part of the A ring compared to its outer part, consistent with the A ring normal optical depth properties The responses of the ionosphere to the B ring shadow is variable, implying different proton production rate and ionospheric plasma transport